Constraints in the accessibility and use of germplasmcollections - Ng, N.Q.; Padulosi, S. (1992)
This paper discusses the problems associated with the lack of precise techniques for measuring the diversity of a crop species, selecting materials for accession, and determining the appropriate size for a core collection, as well as the boundaries of a genepool. The authors list the most important constraints to accessibility and use of germplasm collections, and indicate areas where biotechnology techniques can offer help. Among the research areas considered important for better utilization of germplasm are taxonomy of wild species, techniques for determination ofa representative collection, reproductive biology and germplasm enhancement, conservation techniques and genetic stability under storage, evaluation for specific agronomic traits (particularly for stress resistance), and non-destructive pathogen testing techniques.